Adsorption and reusability performance of M-Fe (M = Co, Cu, Zn and Ni) layered double hydroxides for the removal of hazardous Eriochrome Black T dye from different water streams. (August 2021) - Zubair, Mukarram; Aziz, Hamidi Abdul; Ahmad, Mohd Azmier; Ihsanullah, Ihsanullah; Al-Harthi, Mamdouh A.
Graphical abstract: Highlights: M-Fe (M = Co, Cu, Ni, Zn) LDH possessed a large surface area and excess functional groups. CuFe showed better removal of EBT dye than CoFe, NiFe and ZnFe LDH. The adsorption capacity of EBT onto CuFe LDH was 250 mg/g. EBT adsorption mechanism onto M-Fe LDH involved chemisorption and physisorption processes. Effective regeneration of spent M-Fe LDH was achieved using 0.5 M NaOH. Abstract: In this study, layered double hydroxides (LDHs) containing M (Co, Cu, Zn and Ni) and Fe were produced and employed for the removal of Eriochrome Black T (EBT) dye from different water matrices. The characterization results showed that the CuFe and CoFe LDH exhibited excellent crystallinity and excess surface hydroxyl groups with better textural properties compared to ZnFe and NiFe LDH. Adsorption of EBT onto M-Fe LDH was found higher in the acidic pH range (2−4). The EBT adsorption process onto M-Fe LDH followed the pseudo-second order kinetic model, and isotherm was better described by the Redlich-Peterson (R-P) model. The maximum adsorption capacity of CoFe, CuFe, ZnFe and NiFe LDH was 136.98, 250, 123.45, 123.43 mg/g, respectively at initial dye concentration of 200 mg/L, pH 2.5, contact time 120 min and temperature 298 K. The mean free energy calculated from D–R model was >40 kJ/mol for CoFe and CuFe LDH and <40 kJ/mol for ZnFe and NiFe LDH, implying that the removal of EBT was achieved by chemisorption and physisorption, respectively. The adsorption performance of prepared LDHs after three successive regeneration cycles followed the order: CuFe> CoFe > NiFe > ZnFe. Interestingly, compared to other LDHs, CuFe LDH exhibited better physicochemical properties and showed higher adsorption and reusability performance for the removal of EBT dye in the different water matrices. This indicated that the CuFe LDH could be applied as an effective adsorbent for decontamination of anionic dyes in industrial effluents.